Internal Quality Assurance Management To Improve Graduate Absorption - ulfiah; Wiwik Dyah Ariyani; hanafiah; Fitriyani Kosasih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is motivated by the inability of Vocational School to guarantee the academic quality of its graduates according to the National Education Standards). The method used in this research is a case study method. The results showed that: 1) Planning (Plan) was in accordance with school quality planning procedures, but they still did not understand the stages of quality assurance. 2) In its implementation (Do) there are still State Vocational High Schools that have not formed an Education Quality Assurance Team for Education Units. 3) Monitoring and evaluation in State Vocational Schools has been carried out but quality audit activities are not carried out procedurally by quality auditors. 4) State Vocational High Schools have compiled corrective actions that are outlined in the Work Plan and School Budget and made based on the results of monitoring and evaluation. 5) Almost all State Vocational High School graduates already have a competency certificate from the Professional Certification Institute-P1, but the percentage of State Vocational High School graduates who get a job within one year after graduation only reaches 50%. 6) The obstacle faced is the lack of understanding and awareness of the Principal in improving student academic quality assurance. The solution for State Vocational Schools is to implement a quality assurance system model in stages, systematically and continuously. The conclusion of this study is that in principle, State Vocational Schools have implemented a quality management system but have not succeeded